(untitled) (Modern education and development, 2024)
This article explains the importance of learning English in today’s globalized world. It highlights the role of English in international communication, education, and career opportunities. Additionally, the article discusses its impact on access to information, cultural exchange, and personal development. In conclusion, English is presented not only as a practical skill but also as a fundamental tool for achieving success in a connected and competitive world.